PERAN KOMUNIKASI TERAPEUTIK DALAM BIMBINGAN KONSELING ISLAM: SOLUSI UNTUK KEKHAWATIRAN KARIR GEN Z [THE ROLE OF THERAPEUTIC COMMUNICATION IN ISLAMIC COUNSELING GUIDANCE: A SOLUTION TO GEN Z CAREER CONCERNS] - Ilahiya, Nabila Fadlla; Arifin, Isep Zainal; Wahyuddin, Aef (Perkumpulan Ahli Bimbingan dan Konseling Islam Indonesia, 2025)
This study aims to analyze the role of therapeutic communication in Islamic counseling guidance to address career anxiety faced by Generation Z. Utilizing a literature review method with a descriptive-qualitative approach, this study integrates data from relevant scholarly journals, articles, and textbooks. The analysis was conducted using thematic techniques to identify the key concepts of therapeutic communication and its relevance to career counseling in Islam. The findings indicate that therapeutic communication plays a significant role in building empathetic relationships between counselors and clients through elements such as empathy, openness, and active listening. In the Islamic context, this approach emphasizes spiritual values such as tawakal (trust in God), rahmah (compassion), and ikhtiar (effort), which help Generation Z face career anxiety more calmly and purposefully. A holistic approach that integrates spiritual and psychological values is also proven effective in assisting clients in overcoming career dilemmas and building their confidence. This study concludes that the integration of therapeutic communication in Islamic counseling guidance can provide holistic solutions to the career challenges of Generation Z. It not only focuses on psychological issues but also strengthens the clients' spiritual relationship with God, creating emotional balance and providing motivation to face life’s challenges.